INTEGRATING INTERNAL QUALITY MANAGEMENT AND INSTITUTIONAL PERFORMANCE: EVIDENCE FROM A CONTINUOUS IMPROVEMENT FRAMEWORK - Fatah Nurdin; Albert Wolter Aridan Tangkudung; Yuliasih Yuliasih; Maulana Amirul Adha (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2026)
Improving the quality of higher education governance requires universities to ensure the implementation of the Internal Quality Assurance System (SPMI) is effective and aligned with the achievement of Key Performance Indicators (KPI). This study aims to analyze the implementation of the Determination-Implementation-Evaluation-Control-Improvement cycle in SPMI and examine its relationship to KPI performance at Jakarta State University. A qualitative approach with a case study design was used through in-depth interviews, quality document analysis, observation of SPMI Online and KPI Dashboard, and focus group discussions, then analyzed using thematic analysis techniques. The results show that the quality cycle has been implemented in all units, but there are variations in the consistency of evaluation, follow-up, and documentation, while the use of digital systems has been proven to strengthen the traceability of quality evidence and the relevance of SPMI to KPI achievement. This study contributes by providing an empirical understanding of the relationship between internal quality management and institutional performance and offers a digital-based quality strengthening framework for universities in the era of educational transformation.